Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1464-410x.2010.09994.x
|View full text |Cite
|
Sign up to set email alerts
|

The suburethral tension adjustable sling (REMEEX system) in the treatment of female urinary incontinence due to ‘true’ intrinsic sphincter deficiency: results after 5 years of mean follow‐up

Abstract: • The Remeex system produced remarkable 5-year results with a low complication rate. These outcomes have also been confirmed in a worse prognosis patient group as reported in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
(57 reference statements)
2
17
1
2
Order By: Relevance
“…The subjective cure rate and objective cure rate was 82.0%, 92.5% in 6-month follow-up and 82.3%, 91.2% in 12 month follow-up respectively. The success rates of our study are comparable with previous studies in the literature, which reported similar patientreported and objective success rates of 80-91% in various countries, with varying cohort sizes and lengths of follow-up (6-12 months) [7,8,[11][12][13][14][15][16][17][18][19]. Evidence of longer-term outcomes for the adjustable anchored SIMS is now emerging.…”
Section: Commentssupporting
confidence: 86%
“…The subjective cure rate and objective cure rate was 82.0%, 92.5% in 6-month follow-up and 82.3%, 91.2% in 12 month follow-up respectively. The success rates of our study are comparable with previous studies in the literature, which reported similar patientreported and objective success rates of 80-91% in various countries, with varying cohort sizes and lengths of follow-up (6-12 months) [7,8,[11][12][13][14][15][16][17][18][19]. Evidence of longer-term outcomes for the adjustable anchored SIMS is now emerging.…”
Section: Commentssupporting
confidence: 86%
“…Además presentan ventajas en cuanto a la reproductibilidad de la cirugía, facilidad de colocación y bajas tasas de complicaciones, tanto en mujeres como en pacientes varones con IUE tras someterse a una intervención de prostatectomía 11 . La capacidad de los sistemas Remeex ® para ser reajustados de manera no invasiva durante y después de la intervención es una de sus principales ventajas y de sus mejores características, la cual ha contribuido a la popularidad de este sistema 12 .…”
Section: Discussionunclassified
“…Complicaciones generales (las relacionadas con cualquier procedimiento quirúrgico): hematoma postoperatorio 13,16 , infección de la herida quirúrgica 10,12,14 , dolor postoperatorio. Éste último es mencionado pero no parece resultar de especial significación en este tipo de procedimiento 13 más allá del esperable por la manipulación de la piel y los tejidos blandos de la zona.…”
Section: Discussionunclassified
“…Giberti et al evaluated the objective and subjective outcomes of the Remeex system for SUI caused by ISD in 30 patients, retrospectively [22]. Mean follow-up was 60.6 months.…”
Section: Remeex Systemmentioning
confidence: 99%